Measuring the underwater received power behavior for 433 mhz radio frequency based on different distance and depth for the development of an underwater wireless sensor network - Muhammad Ramdhan M.S; Muhammad Ali; Nurzal Effiyana G; Samura Ali; Kamaludin M.Y (Institute of Advanced Engineering and Science, 2019)
Underwater wireless sensor network (UWSN) important to enhance the widely use of the application of the Internet of things (IoT) for underwater. Uses of the acoustics base of wave propagations are the best ways to establish the UWSN. But the unpracticality of the hardware due to the size and cost has limited the application of UWSN. Radio frequency (RF) wave propagation is the best way to overcome this situation. Low frequency of the RF wave is proven feasible and suitable for underwater communication. 433 MHz RF were chosen to measuring the underwater received power behavior between the transmitter node and receiver node based on different distance and depth. HC12 transceiver module was used as a transmitter and spectrum analyzer with the telescopic antenna was used as a receiver. The received power give a good reading when the transmitter note was at 0.5-meter depth with a maximum operating range within 12 meters from the receiver.